Extracting individual solar cell data from photovoltaic module electroluminescence images and current-voltage curves - Suca de Azevedo, Alexia (2024)
Electroluminescence (EL) imaging is explored as a non-destructive method for quality assessment and characterization of solar modules. Here, we demonstrate the acquisition of dark I(V) characteristics for each individual cell within a solar photovoltaic module from complete module EL images. This enables a detailed diagnosis of module failure by individualizing cell parameters, such as series resistance and dark saturation current density. Such analyses become increasingly important with module aging, enhancing the possibilities for module or cell recycling. The method is checked for consistency with module parameters extracted from the measured module dark I(V) characteristics.